Characteristics and Clinical Outcome of Management of Chronic Heart Failure Reduced Ejection Fraction in Patients with Chronic Kidney Disease Compared to Non-Chronic Kidney Disease Patients that Follow Up in Dedicated Heart Failure Clinic – Multicenter Observational Study - Chan, En Ze; Chung, Bui Khiong; Ling, Hwei Sung; Chow, Han Bing; How Kiat, Khor; Andy Tze Yang, Ko; Chiang, Kit How; Leong, Lai Kuan; Pang, Ing Xiang; Julian Wei Ee, Tong; Cheah, Cheng Foong; Esteban Yu Hern, Chin; et al. (Elsevier B.V., 2024)
The presence of chronic kidney disease(CKD) in patients with heart failure (HF) can increase the rates of complications, readmissions and mortality. Patients with CKD can also limit the use of guideline-directed medical therapy(GDMT) for HF in regular clinical practice. The clinical outcome of HF patients with CKD compared to non-CKD in a dedicated HF clinic is unknown.